Analysis of Factors Affecting Audit Quality at The Bogor District Inspectorate: The SEM-PLS Approach - Iryani, Lia Dahlia; Rahman, Aisyah Abdul; Yadiati, Winwin (Akuntansi: Jurnal Akuntansi Integratif, 2026)
Purpose: Audit quality is a fundamental component of effective governance, particularly within the public sector, where internal supervisory bodies play a critical role in ensuring accountability and transparency. Recent corruption cases in the Bogor District have illuminated significant shortcomings in the internal audit mechanisms, thereby necessitating a comprehensive exploration of the factors that influence audit quality. This study aims to investigate the effects of education, professional experience, and professionalism on audit quality within the Bogor District Inspectorate. Methodology/approach: Employing SEM-PLS, the study analyzed data obtained from a survey of 36 professional auditors. Findings: The findings indicated that professional experience has a significant positive impact on audit quality, whereas education and professionalism do not exhibit statistically significant direct effects. These results suggested that, while academic qualifications and professional attitudes remain important, practical experience is a more decisive factor in enhancing audit quality. Practical implications: The research provided meaningful guidance for public sector audit institutions aiming to improve audit effectiveness by strengthening the competencies of their auditors. Originality/value: This study provides empirical evidence from a local government context, highlighting the dominant role of professional experience in determining audit quality. Future research is encouraged to explore potential mediating or contextual factors influencing these relationships.